The Self-reliance of Micro Business Agents at Nagrak Village Darangdan Sub District Purwakarta District - Nurrohmi Nurrohmi (Politeknik Kesejahteraan Sosial Bandung, 2023)
Self-reliance is readiness and capacity of individual to stand alone characterized by taking initiatives, solving problems without other people’s help. Self-reliance is usually characterized by taking self-determination, being creative, and initiative, organizing behavior, taking responsibility, and being able to control himself. This research aimed to describe self-reliance of micro business agents consisting of seven aspects. This study used descriptive qualitative method. 45 respondents were obtained using simple random sampling technique. Data collection used questionnaires and document study. Data were analyzed by descriptive statistic. The results showed that the self-reliance of the micro business agents was categorized very high. Independence aspect was 1119 of the 1260 ideal score; Initiative aspect was 990 of the 1260 ideal score; Self-confidence aspect was 1116 of the 1260 ideal score; Responsibility aspect was 1135 of the 1260 ideal score; Self-assertiveness was 1089 of the 1260 ideal score; Decision making was 1069 of the 1260 ideal score; and Self-control aspect was 1117 of the 1440 ideal score. From the seven aspects, Initiative was the lowest one with 990 of the 1260 ideal score. It needs to be developed. Nevertheless, the Self-reliance of the micro business agents at Nagrak village, in general, is still very high.